Vacancy migration energies in CrMnFeCoNi, CrFeCoNi, and CrFeNi alloys and their effect on atomic diffusion. (1st February 2022) - Sugita, Kazuki; Ogawa, Ryusei; Mizuno, Masataka; Araki, Hideki; Yabuuchi, Atsushi
Highlights: The vacancy migration energies in equimolar CrMnFeCoNi, CrFeCoNi, and CrFeNi alloys were investigated by positron annihilation lifetime spectroscopy. The migration energies of monovacancies in CrMnFeCoNi, CrFeCoNi, and CrFeNi alloys were evaluated to be 0.93, 0.92, and 0.79 eV, respectively. The vacancy migration energies increase with the number of constituent elements among these three alloys, however were slightly smaller than in pure Ni. It suggests the possibility of shallow vacancy trapping by local chemical environments in the CrMnFeCoNi alloy. These results do not fully support the sluggish diffusion mechanism that has been proposed for high-entropy alloys. Abstract: The mechanism of sluggish diffusion in high-entropy alloys has not been understood completely. In this study, we aimed to understand the mechanism by estimating the vacancy migration energies in such alloys. The vacancy migration and annihilation behavior in equimolar CrMnFeCoNi, CrFeCoNi, and CrFeNi alloys during an annealing process after electron irradiation were investigated via positron annihilation lifetime spectroscopy. The migration energies of monovacancies in these alloys were evaluated to be 0.93, 0.92, and 0.79 eV, respectively, which are comparable with or slightly smaller than that in pure Ni, one of the constituents metals that has the same face-centered cubic structure. On the other hand, the vacancy migration energies increase with the number of constituent elements, suggesting the possibility of shallow vacancy trapping by local chemical environments in the CrMnFeCoNi alloy. These results do not fully support the sluggish diffusion mechanism that has been proposed for high-entropy alloys. Graphical abstract: Image, graphical abstract